PENGARUH KEMAMPUAN KERJA PEGAWAI DAN IKLIM ORGANISASI DENGAN EFEKTIVITAS ORGANISASI DI BALAI REHABILITASI SOSIAL MARDI UTOMO SEMARANG I - Pertiwi, Khoiriyah Sari; Widowati, Nina; Rihandoyo, Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Organizational effectiveness is the attainment of the goal that had been developed by an organization. This research aims to know the affect of employee working ability and organizational climate with organizational effectiveness in the Social Rehabilitation Center Mardi Utomo Semarang I. Researcher used explanatory research type by distributing an open questionnaire to collect data from 21 respondents. This research using Pearson product moment correlation analysis to measure hypothesis. The result of this research through product moment correlation formula shows that level of the relation between the variables of employee working ability with organizational effectiveness with score 0.675, organizational climate with organizational effectiveness with score 0.680, employees working ability and organizational climate with organizational effectiveness with score 0.742, so there’re in the category of strong . According to the t test showed that employee working ability (X1) affect organizational effectiveness (Y) with score 3.985, organizational climate (X2) affect organizational effectiveness (Y) with score 4.041 and there is a positive and significant affect the employees working ability (X1) and organizational climate (X2) with organizational effectiveness (Y) on the score 11.044. In conclusion showed a positive and significant effect between employee working ability and organizational climate with organizational effectiveness. It’s mean that to improve the effectiveness of the organization in the Social Rehabilitation Center Mardi Utomo Semarang I needed a few things to do like holding discussions with the social educational institutions, deepening of the process of social and rehabilitation services, an evaluation of services to receiver, increase the level of communication and give an award from the leader as a form of attention.